(untitled) (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Psoriasis is multifactorial in origin. Streptococcal infection, sore throat has been claimed to be an infectious cause. Objective: The purpose of the present study was to observe the association of Streptococcus with guttate psoriasis. Methodology: This was an observational case-control study which was conducted in the Department of Dermatology & Venereology at Bangabandhu Sheikh Mujib Medical University (BSMMU), & Shaheed Suhrawardy Medical College hospital (ShSMCH) in Dhaka city of Bangladesh during the period of February 2012 to October 2012. Patients clinically and histopathologically diagnosed as psoriasis were selected as case group and patients with skin diseases other than psoriasis were selected as control group. Results: A total of 115 patients were included in this study of which 64 patients were in case group and the rest 51 patients were designated as control group. The mean age was 30.73±14.69 years and 26.47±12.64 years in cases and control groups respectively (p>0.05). About 66.6% patients gave a positive history of sore throat. ASO titer was raised (>200 IU/ml) in 25(83.3%) patients of guttate psoriasis and 5(23.8%) in patients of their non-psoriatic controls (p<0.05). Streptococcus pyogenes was found in 9(30.0%) patients of case group and only 2(9.5%) patients were found in their control group. Conclusion: Streptococcal throat infections are associated with guttate psoriasis patients. DOI: http://dx.doi.org/10.3329/jssmc.v5i2.20763 J Shaheed Suhrawardy Med Coll, 2013;5(2):91-94